2015
DOI: 10.1007/s00059-015-4303-6
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 als neuer Biomarker diastolischer Funktionsstörung bei Hämodialysepatienten

Abstract: We suggest that gal-3 may be a promising biomarker for the detection of LVDD in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…This study revealed a continual relationship after adjustment for age, LVEF, and NT-proBNP [ 28 ] and further implied that it is renal impairment (with signs of inflammation and fibrosis) that contributes to the prognostic properties of Gal-3 in HFpEF. Supplementary work by Gurel et al [ 29 ] suggested the potential use of Gal-3 in detecting HFpEF in patients undergoing hemodialysis. The present results demonstrate a significant relationship between Gal-3 levels and patient serum creatinine values across the entire HFpEF spectrum of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a continual relationship after adjustment for age, LVEF, and NT-proBNP [ 28 ] and further implied that it is renal impairment (with signs of inflammation and fibrosis) that contributes to the prognostic properties of Gal-3 in HFpEF. Supplementary work by Gurel et al [ 29 ] suggested the potential use of Gal-3 in detecting HFpEF in patients undergoing hemodialysis. The present results demonstrate a significant relationship between Gal-3 levels and patient serum creatinine values across the entire HFpEF spectrum of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing maintenance hemodialysis (HD), serum galectin-3 levels were correlated with early velocities/early diastolic mitral annular velocities (E'), left atrial volume index, and E'. Further analysis demonstrated that galectin-3 may be used in the diagnosis of LV diastolic function with a sensitivity and specificity of 67.6 and 84.6%, respectively ( 108 ). Serum galectin-3 levels were also revealed to be associated with LV hypertrophy independent of left ventricle geometry in patients with HD, as well as in the general population ( 109 ).…”
Section: Galectin-3 and Renal Diseasementioning
confidence: 99%
“…Wu et al [25] reported correlations between plasma galectin-3 and E/E' in advanced HFpEF. Gurel et al [26] demonstrated that galectin-3 was an independent predictor of DD in patients with end-stage renal failure undergoing dialyses. Another study compared serum levels of galectin-3 in patients with HFrEF and HFpEF and demonstrated that it was higher in patients with HFrEF and correlated with E/E' ratio [27].…”
Section: Kinetics Of Tgf Ctgf and Galectin-3 In Patients With Varioumentioning
confidence: 99%